MUSIC Based Microwave Imaging of Nonlinear Point-Like Scatterers - Utku, Cüneyt (Fırat University, 2022)
Narrowband localization of point-like nonlinear scatterers in a homogeneous background medium is investigated. A theoretical framework is provided based on Multiple Signal Classification (MUSIC) imaging, formerly developed for time-reversal imaging of point-like targets in cluttered environment. Numerical simulations are provided to assist in understanding the relations between various aspects of the imaging method. Numerical evidence shows that for the same signal to noise ratio, higher order harmonics (second and third harmonics) resulting from nonlinear scattering, have better imaging resolutions compared to the fundamental harmonic corresponding to linear scattering.
Keywords: Engineering; Mühendislik